Microsatellite Instability (MSI) as an Independent Predictor of Pathologic Complete Response (PCR) in Locally Advanced Rectal Cancer: A National Cancer Database (NCDB) Analysis. Issue 4 (April 2020) - Hasan, Shaakir; Renz, Paul; Wegner, Rodney E.; Finley, Gene; Raj, Moses; Monga, Dulabh; McCormick, James; Kirichenko, Alexander
Abstract : Objective: The relationship between microsatellite instability (MSI) and response to neoadjuvant chemoradiation in rectal cancer is not well understood. Background: We utilized the National Cancer Database (NCDB) to investigate the association between MSI and pathologic complete response (pCR) in this patient population. Methods: We analyzed 5086 patients between 2010 and 2015 with locally advanced rectal cancer who were tested for MSI and treated definitively with chemoradiation followed by surgery. Primary comparison groups were between 4450 MSI-negative(−) and 636 MSI-positive(+) patients. Multivariable regression analysis was conducted to identify demographic, therapeutic, and clinical characteristics predictive of pCR. Cox proportional-hazard ratios were used for survival. Results: All patients were treated with definitive chemoradiation (median dose 50.4 Gy) followed by resection within 4 months. MSI(+) patients were associated with earlier year of diagnosis and higher-grade tumors ( P < 0.05). The overall pCR rate was 8.6%, including 8.9% for MSI(−) and 5.9% for MSI(+) tumors ( P = 0.01). Along with lower T stage, MSI(+) cases were significantly associated with a reduced pCR rate (odds ratio 0.65, 95% confidence interval 0.43–0.96) with multivariable analysis. The 5-year survival for patients with pCR was 93% compared with 73% without it (<0.001). Conclusion: Microsatellite instability was independently associated with a reduction in pCR for locally advanced rectal cancer after neoadjuvant chemoradiation in this NCDB-based analysis.